2017
DOI: 10.1039/c7cc01985h
|View full text |Cite
|
Sign up to set email alerts
|

Tracking thermal-induced amorphization of a zeolitic imidazolate framework via synchrotron in situ far-infrared spectroscopy

Abstract: We present the first use of in situ far-infrared spectroscopy to analyze the thermal amorphization of a zeolitic imidazolate framework material. We explain the nature of vibrational motion changes during the amorphization process and reveal new insights into the effect that temperature has on the Zn-N tetrahedra.Vibrational spectroscopy has been shown to be an excellent method of analyzing framework materials and gaining a better understanding of their molecular structure. The mid-infrared (MIR) region of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…By distorting the framework and reducing its symmetry according to the A2g normal mode, we could find a symmetry‐reduced lattice configuration (space group Fm3¯) and resolve the structural instability on compression. This is shown in Figure where the middle panel is a graphical representation of the A2g normal mode, that can be described as a simultaneous deformation of the ZnO polyhedra (similar to that previously reported to be linked to the mechanical and thermal instability of other Zn‐based MOF materials) and rotation of the organic linkers. This mode is also clearly linked to the mechanism underlying the NTE of the framework .…”
Section: Resultssupporting
confidence: 56%
“…By distorting the framework and reducing its symmetry according to the A2g normal mode, we could find a symmetry‐reduced lattice configuration (space group Fm3¯) and resolve the structural instability on compression. This is shown in Figure where the middle panel is a graphical representation of the A2g normal mode, that can be described as a simultaneous deformation of the ZnO polyhedra (similar to that previously reported to be linked to the mechanical and thermal instability of other Zn‐based MOF materials) and rotation of the organic linkers. This mode is also clearly linked to the mechanism underlying the NTE of the framework .…”
Section: Resultssupporting
confidence: 56%
“… 6 These and related studies concluded that for these materials the mechanical properties can be described with the low density–stiffness correlation. 6 , 29 32 As these experiments require sufficiently large single crystals, the number of studied structures is relatively small compared to the total number of possible ZIFs. In this work, we expand the studied materials to, in addition to the known ZIF structures, a large set of in silico constructed materials using 50 different zeolite topologies 33 with four types of ligands.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks located at 1681-1475 cm À1 are characteristic of CQC, CQN and imidazolate ring stretching. 20,21 Both the decreased absorption of the peak near 1680 cm À1 and the increased absorption of the associated weak peak near 1600 cm À1 indicate possible distortion of the imidazolate rings in the ZIF-4 glass upon melt-quenching and heat-treatment. This is further confirmed by the noticeable change of the C-H bending peak near 1387 cm À1 .…”
Section: Researcher Informationmentioning
confidence: 99%